BABURNAMA – THE TREASURE OF WORLD LITERATURE, CULTURE AND ART (Modern education and development, 2024)
This article talks about the place of Zahiriddin Muhammad Babur in the history of world politics and culture, and the position of his work "Boburnoma" in world oriental studies and in the history of world translation studies.